STRATEGI POSITIONING DALAM PENINGKATAN DAYA SAING LEMBAGA (Studi Kasus di Raudlatul Athfal Ulul Albab Kaliwates Jember) - Abdullah; Siti Aminah; Muhammad Suwignyo Prayogo (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2022)
In this decade Raudlatul Athfal is no longer an alternative to kindergarten schools, but RA is the choice of the community so that it is called "RA is TK Plus". However, in 2019 it was stated that out of 1000 institutions registering early childhood education units at the East Java level, only less than 10 RA institutions received an A accreditation. Therefore, it is time for Islamic educational institutions, especially RA, to start making improvements to have competitiveness. The positioning strategy is an institution's effort to increase competitiveness. Raudlatul Athfal Ulul Albab Kaliwates Jember received an excellent A accreditation in 2019, and various achievements, namely the inspirational RA at the East Java level (2019), the school principal being the 1st Winner of the best RA principal at the East Java level to the National level (2018) and the development of the number of Students are increasing year by year, this is because RA Ulul Albab has a positioning strategy to have competitiveness. Therefore, this study aims to describe the positioning strategy and positioning communication strategy of the principal in increasing competitiveness at the RA Ulul Albab school. In this study, the author uses a descriptive qualitative approach with the type of case study research. While the results of this study are the first Positioning Strategy in Increasing Competitiveness at the RA Ulul Albab School seen from the potential of institutional resources in urban areas, the institutional advantage is seen from the concept of religious-based multiple intelligences, the love of teachers to participants students, establish good relations with parents. Meanwhile, institutional marketing is by building communication both verbally and in writing, both direct communication and through social media such as posters, flyers, banners and others by offering institutions as institutions that introduce religion from an early age. The second is the Principal Positioning Communication Strategy in Improving Competitiveness at the RA Ulul Albab School, namely the principal in building organizational strength acting as a planner, manager, supervisor and communicator. The communication pattern strategy built by the principal was more intense through visiting activities from other institutions, and to communicate in building the achievements of the teacher council, the principal of RA Ulul Albab gave praise to all teachers when there were teachers who did creative things without being asked or told.   Keywords: Positioning Strategy, Competitiveness, Raudlatul Atfhal.   Pada dekade ini Raudlatul Athfal bukan lagi menjadi alternatif sekolah TK, akan tetapi RA adalah pilihan masyarakat hingga disebut “RA adalah TK Plus”. Namun, tahun 2019 dinyatakan bahwa dari 1000 lembaga daftar satuan pendidikan anak usia dini tingkat Jawa Timur  hanya kurang dari 10 lembaga RA yang mendapat nilai akreditasi A. Olah karena itu, saatnya lembaga pendidikan Islam khususnya RA mulai melakukan pembenahan agar memiliki daya saing. Strategi positioning adalah sebagai upaya lembaga  dalam meningkatkan daya saing. Raudlatul Athfal Ulul Albab kaliwates Jember mendapatkan akreditasi A unggul pada tahun 2019, dan pelbagai prestasi yang diraih yakni RA inspiratif tingkat Jawa Timur (2019) , kepala sekolahnya menjadi Juara 1 kepala sekolah RA terbaik tingkat Jawa Timur hingga Tingkat Nasional (2018) dan perkembangan jumlah siswa semakin tahun semakin bertambah, hal ini karena RA Ulul Albab memiliki strategi positioning hingga memiliki daya saing. Oleh karena itu penelitian ini bertujuan mendeskripsikan strategi positioning dan strategi komunikasi positioning kepala sekolah dalam peningkatan daya saing di sekolah RA Ulul Albab. Dalam penelitian ini, penulis menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian studi kasus. Sedangkan hasil dari penelitian ini yang pertama Strategi Positioning dalam Peningkatan Daya Saing di Sekolah RA Ulul Albab dilihat dari Potensi resources lembaga yang berada di daerah perkotaan, Keunggulan kelembagaanya dilihat dari konsep kecerdasan majemuk (Multiple Intelligence) berbasis keagamaan, kasih sayang guru-guru kepada peserta didik, menjalin hubungan baik dengan walimurid. Sedang pemasaran lembaga dengan membangun komunikasi baik lisan maupun tulisan baik komunikasi langsung maupun melalui media sosial seperti poster flayer banner dan lain-lain dengan menawarkan lembaga sebagai lembaga yang mengenalkan agama sejak dini. Yang kedua Strategi Komunikasi Positioning Kepala Sekolah dalam Peningkatan Daya Saing di Sekolah RA Ulul Albab, yakni Kepala sekolah dalam membangun kekuatan organisasi berperan sebagai perencana, manajer, supervisor dan komunikator. Strategi pola komunikasi yang dibangun oleh kepala sekolah lebih intens melalui kegiatan kunjungan dari lembaga lain, dan untuk berkomunikasi dalam membangun prestasi dewan guru, kepala sekolah RA Ulul Albab memberikan pujian kepada seluruh guru ketika ada guru yang melakukan hal yang kreatif dengan tanpa diminta atau disuruh.   KataKunci: Strategi Positioning, Daya Saing, Raudlatul Atfhal.